Sub-100 nm wrinkling of polydimethylsiloxane by double frontal oxidation - Nania,M; Foglia,F; Matar,OK; Cabral,JT (Nanoscale, 2017)
We demonstrate nanoscale wrinkling on polydimethylsiloxane (PDMS) at sub-100 nm length scales via a(double) frontal surface oxidation coupled with a mechanical compression. The kinetics of the glassy skinpropagation is resolved by neutron and X-ray reflectivity, and atomic force microscopy, combined withmechanical wrinkling experiments to evaluate the resulting pattern formation. In conventional PDMSsurface oxidation, the smallest wrinkling patterns attainable have an intrinsic lower wavelength limit dueto the coupling of skin formation and front propagation at fixed strain εprestrain, whose maximum is, inturn, set by material failure. However, combining two different oxidative processes, ultra-violet ozonolysisfollowed by air plasma exposure, we break this limit by fabricating trilayer laminates with excellent interfacialproperties and a sequence of moduli and layer thicknesses able to trivially reduce the surface topographyto sub-100 nm dimensions. This method provides a powerful, yet simple, non-lithographicapproach to extend surface patterning from visible to the deep UV range.